2016
DOI: 10.1016/j.surfcoat.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrical parameters on particle uptake during plasma electrolytic oxidation processing of AM50 Mg alloy

Abstract: The influence of electrical parameters on microstructure and composition of coatings by plasma electrolytic oxidation (PEO) with particle addition was investigated. PEO coatings were produced on AM50 magnesium alloy from an alkaline phosphate based electrolyte (1 g/l KOH + 20 g/l Na 3 PO 4 ) with 5 g/l SiO 2 particle (1-5 µm) addition. Besides the most common electrical parameters (voltage and current density), frequency and duty ratio have effect on the uptake of particles during PEO processing. Higher duty r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 29 publications
6
16
0
Order By: Relevance
“…Whereas, Sandhyarani et al have observed dense oxide layer with negligible porosity at lower frequency, and porous layer at higher frequency on Zr substrate. Similarly, Lu et al have also observed the increase in number of pores and decreased coating thickness with higher frequency at constant duty cycle on Mg alloy as shown in Figure (g–l). Duty cycle, which is the ratio in percentage form between on‐duration in a pulse cycle to the total duration of cycle, exhibits a positive correlation with pore enlargement .…”
Section: Plasma Electrolytic Oxidationsupporting
confidence: 57%
See 2 more Smart Citations
“…Whereas, Sandhyarani et al have observed dense oxide layer with negligible porosity at lower frequency, and porous layer at higher frequency on Zr substrate. Similarly, Lu et al have also observed the increase in number of pores and decreased coating thickness with higher frequency at constant duty cycle on Mg alloy as shown in Figure (g–l). Duty cycle, which is the ratio in percentage form between on‐duration in a pulse cycle to the total duration of cycle, exhibits a positive correlation with pore enlargement .…”
Section: Plasma Electrolytic Oxidationsupporting
confidence: 57%
“…Similarly, Lu et al have also observed the increase in number of pores and decreased coating thickness with higher frequency at constant duty cycle on Mg alloy as shown in Figure (g–l). Duty cycle, which is the ratio in percentage form between on‐duration in a pulse cycle to the total duration of cycle, exhibits a positive correlation with pore enlargement . Partial dissolution of PEO coatings occur at elevated temperature of electrolyte, resulting in thinner coatings …”
Section: Plasma Electrolytic Oxidationsupporting
confidence: 57%
See 1 more Smart Citation
“…For instance, it has been shown that the coating corrosion behaviour is improved with the addition of ZrO 2 [12] or CeO 2 [13] particles, whereas the incorporation of Al 2 O 3 [14], TiO 2 [15], SiC [16] and SiO 2 [17] improves mechanical properties. Lu et al [18] revealed that the particle uptake from the electrolyte depends greatly on the electrical parameters, more specifically on the frequency of pulsed current used for the coating formation. Particle incorporation is deemed to occur via the molten pools formed at the microdischarge sites; therefore, higher pulse frequencies would usually result in a lower particle uptake, as less intense microdischarges melt smaller volumes of material on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the incorporated particles would usually suffer from superficial modifications as a result of the high temperature and pressure developed within the plasma microdischarge. From general considerations [18], the extent of modification, which defines the mode of particle incorporation -reactive or non-reactive (inert) -would depend on the nature of the particle and metallic substrate, electrolyte composition and electrical parameters of the PEO process. In the case of nano-containers, inert incorporation is essential; however, there is no clear understanding at the moment how this can be achieved under the extreme conditions developed at the sites of microdischarges that might compromise container integrity.…”
Section: Introductionmentioning
confidence: 99%